The impact of globalization and convergence on the development of media industries - Milenković, Vesna (Napredak, 2022)
Globalization and convergence, as two phenomena that change the image of the media world and affect the development of media industries due to their ambiguity, are a consequence not only of technological development, but can also be interpreted from political, economic and cultural aspects. Analyzed within such context, media industries are becoming one of the most important factors that have an active impact on people’s lives by striving to change and run them. This paper deals with the impact of convergence and global change on the development of media industries, given the fact that the media, on the one hand, as part of the act of communication, constitute intermediaries transmitting information, while, on the other hand, they produce and market their goods just as any other industry does. It is stated in the conclusion that these two phenomena of the digital era are crucial both to the development of the media industry and the work of the media as intermediaries transmitting information, create it and distribute content that has long since acquired the features of goods that are marketed. Without media convergence, in global society it would not be possible for each individual who has become a player in international/global communication to independently organize the media culture content and thus actively participate in the political and social life of the digital era.